1993
DOI: 10.1016/0014-5793(93)80898-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of novel isoforms of 6‐phosphofructo‐2‐kinase/fructose‐2,6‐bisphosphatase from bovine heart

Abstract: Distinct 6‐phosphofructo‐2‐kinase (PFK‐2)/fructose 2,6‐bisphosphatase (FBPase‐2) cDNAs were cloned from bovine heart, showing that PFK‐2/FBPase‐2 gene B, which contains 16 exons, codes for at least five mRNAs. Three of them (B1, B2, B4) could encode the 58,000‐M r isozyme. In B2 mRNA, exon 15 encodes four more residues than in Bl. In B4 mRNA, exon 15 encodes six more residues than in B1, butexon 16 (20 residues) is missing. B3 mRNA corresponds to the 54,000‐M r isozyme. It lacks exon 15 and also differs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…The detection of multiple bands in Northern blots probed with the heart-type clone 2kbC5 is consistent with the identification of at least five mRNAs derived from gene B [28]. The entire PFK-2/FBPase-2 heart-type transcript predicted to correspond to 2kbC5 (due to its intense signal in kidney) detected on the Northern blot appeared to be approx.…”
Section: ~-Actinsupporting
confidence: 80%
See 2 more Smart Citations
“…The detection of multiple bands in Northern blots probed with the heart-type clone 2kbC5 is consistent with the identification of at least five mRNAs derived from gene B [28]. The entire PFK-2/FBPase-2 heart-type transcript predicted to correspond to 2kbC5 (due to its intense signal in kidney) detected on the Northern blot appeared to be approx.…”
Section: ~-Actinsupporting
confidence: 80%
“…The differential splicing implied by this result is supported by earlier characterization of the homologous bovine autosomal locus which has been shown to encode at least five mRNAs [28]. Comparison of the mouse heart-type isozyme encoded by 2kbC5 with --9 Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The best characterized are the liver (L), skeletal muscle (M), heart (H), testis (T) and brain isoenzymes. The sequence of the L mRNA of several species is known [30][31][32] as well as that of the rat M-, T-and H-type mRNAs [33][34][35][36]. In addition, a fetal (F)-type mRNA was recently identified [37].…”
Section: Gene Organizationmentioning
confidence: 99%
“…Peptide sequence analysis revealed that the M r 54,000 form lacks phosphorylation sites for PKA (Ser-466 and Ser-483) and protein kinase C (Ser-466 and Thr-475), which are encoded by exon 15 and thus present in the M r 58,000 form (15,17). The situation in bovine heart is further complicated by the fact that four different mRNAs have been characterized (18). One (B3) lacks exon 15 and is therefore similar to the M r 54,000 form.…”
mentioning
confidence: 99%